Main Drivers of Fecundity Variability of Mussels along a Latitudinal Gradient: Lessons to Apply for Future Climate Change Scenarios - Gabriela F. Oliveira; Hanifah Siregar; Henrique Queiroga; Laura G. Peteiro (Journal of Marine Science and Engineering, 2021)
Bivalve relevance for ecosystem functioning and human food security emphasize the importance of predictions of mussel performance under different climate stressors. Here, we address the effect of a latitudinal gradient of temperature and food availability on the fecundity of the Mediterranean mussel to try to better parameterize environmental forcing over reproductive output. We show that temperature plays a major role, acting as a switching on–off mechanism for gametogenesis, while food availability has a lower influence but also modulates the number of gametes produced. Temperature and food availability also show different effects over fecundity depending on the temporal scale evaluated. Our results support the view that the gametogenesis responds non-linearly with temperature and chlorophyll concentration, an issue that is largely overlooked in growth, production and energy budgets of bivalve populations, leading to predictive models that can overestimate the capability of the mussel’s populations to deal with climate change future scenarios.